2011
DOI: 10.1002/cmdc.201000445
|View full text |Cite
|
Sign up to set email alerts
|

Modified 5′‐Trityl Nucleosides as Inhibitors of Plasmodium falciparum dUTPase

Abstract: 2'-Deoxyuridine triphosphate nucleotidohydrolase (dUTPase) is a potential drug target for the treatment of malaria. We previously reported the discovery of 5'-tritylated analogues of deoxyuridine as selective inhibitors of this Plasmodium falciparum enzyme. Herein we report further structure-activity studies; in particular, variations of the 5'-trityl group, the introduction of various substituents at the 3'-position of deoxyuridine, and modifications of the base. Compounds were tested against both the enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Additionally, the absence of the trityl group results in drastic decrease in activity against Pf dUTPase, as observed in compounds 4 and 127 ( Figures 2A,B , respectively), and a clear decrease in selectivity, when we compare compounds 20 and 87 ( Figures 2C,D , respectively). These observations corroborate previous studies ( Whittingham et al, 2005 ; McCarthy et al, 2009 ; Baragaña et al, 2011 ; Hampton et al, 2011 ; Recio et al, 2011 ; Ruda et al, 2011 ; Ojha and Roy, 2013 ), indicating that two of the three phenyl rings from the trityl group have significant interactions with the hydrophobic pocket formed by residues Phe46 and Ile117 from Pf dUTPase ( Hampton et al, 2011 ). In contrast, in the human enzyme, such residues are replaced by hydrophilic residues Val42 and Gly87.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the absence of the trityl group results in drastic decrease in activity against Pf dUTPase, as observed in compounds 4 and 127 ( Figures 2A,B , respectively), and a clear decrease in selectivity, when we compare compounds 20 and 87 ( Figures 2C,D , respectively). These observations corroborate previous studies ( Whittingham et al, 2005 ; McCarthy et al, 2009 ; Baragaña et al, 2011 ; Hampton et al, 2011 ; Recio et al, 2011 ; Ruda et al, 2011 ; Ojha and Roy, 2013 ), indicating that two of the three phenyl rings from the trityl group have significant interactions with the hydrophobic pocket formed by residues Phe46 and Ile117 from Pf dUTPase ( Hampton et al, 2011 ). In contrast, in the human enzyme, such residues are replaced by hydrophilic residues Val42 and Gly87.…”
Section: Resultssupporting
confidence: 91%
“…2D and 3D QSAR models were built using a series of Pf dUTPase inhibitors reported in the literature (Supplementary Table S1 ) ( Nguyen et al, 2005 , 2006 ; Whittingham et al, 2005 ; McCarthy et al, 2009 ; Baragaña et al, 2011 ; Hampton et al, 2011 ; Ruda et al, 2011 ). The data set was prepared and curated according to the protocol described by Fourches et al (2010 , 2015 , 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Tight regulation avoids incorporation of uracil into DNA, which could ultimately cause cell damage and consequently cell death . For this reason, dUTPases have been proposed as possible pharmaceutical targets in cancer cells or pathogenic microorganisms . Furthermore, it was recently found that virus/phage dUTPases could also regulate some cellular processes, acting as signalling molecules .…”
Section: Introductionmentioning
confidence: 99%
“…The authors routinely begin this synthesis with 20 g of thymidine to prepare 6 g (~ 7 mmol) of P6 monomer. This synthetic sequence is based upon published literature with modifications by the authors (Challa & Bruice, 2004;Eleuteri et al, 1996;Lavandera et al, 2001;Ruda et al, 2011). Similar synthetic protocols have been reported for the other bases; however, they have not been verified by the authors (Linkletter et al, 2001;Szabo & Bruice, 2004).…”
Section: Support Protocol 2: Synthesis Of Thiourea Monomermentioning
confidence: 87%